Lawrence of Arabia ([United States] Columbia Pictures, 1962)
A historical drama re-creating the legend of a gifted soldier and true independent spirit, T. E. Lawrence, and his accomplishments in the World War I desert campaign in which he led the Arabs against the Turks in the 1920s.
Disc 1 (1 hr., 20 min.) -- disc 2 (1 hr., 17 min.)
Based on events in the life of T. E. Lawrence.
VCD.
Produced by Sam Spiegel ; directed by David Lean ; screenplay by Robert Bolt.
Cast: Alec Guiness, Anthony Quinn, Jack Hawkins, Jose Ferrer, Anthony Quayle, Claude Rains, Arthur Kennedy, Omar Sharif, and Peter O'Toole.
Keywords: Lawrence, Thomas Edward -- 1888-1935.; World War -- Campaigns -- 1914-1918 -- Middle East; Soldiers -- Great Britain -- Biography; Feature films; Adventure films